Slope Morphology and Impacts on Agricultural Productiviy in the Kom Highlands of Cameroon - Fombe, Lawrence F.; Tossa, Hycinth N. (Advances in Social Sciences Research Journal, 2015)
Very steep and rugged slopes impact significantly on agricultural processes and patterns as characterized by the Kom highland of the Northwest Region of Cameroon. The study examines the aspects of slope morphology that influence agricultural production and how the inhabitations react to slope elements (gradient, soil, climate and altitude) in an effort to increase agricultural productivity and improve on their livelihoods. Primary data was collected through the use of questionnaires, interviews, field observations focus group discussions and measurements. Secondary data on the agro-ecological zones of the study area and soil characteristics was obtained from the Divisional Delegation of Agriculture for Boyo. Information on the slope characteristics, the slope gradients and altitudinal classification was obtained from the topographic maps of the study area and GPS coordinates. The main findings indicate that agricultural practices in the Kom highlands significantly depend on slope morphology which has obliged the mountain dwellers to adopt coping mechanisms such as contour ploughing, mixed cropping and mixed farming in order to minimize the impacts of slope configuration on their farming activities.